Local people's perceptions of Lake Basin water governance performance in Thailand - Peter, Emmanuel Cookey (ScienceDirect, 2016)
Local people's perceptions on water governance performance were explored in the Songkhla Lake Basin, Thailand. The study was conducted through self-administered survey questionnaires, interviews, observations as well as review of relevant literature and archival records. The objective was to understand the perceptions of the local people regarding performance of the water governance of the Songkhla Lake Basin in order to support a wider research assessing the water governance performance of the Lake Basin. The local people perceived the governance performance as below average and highlighted some pertinent challenges such as institutional and agency fragmentation, weak coordination and integration as well as enforcement and compliance. They suggested that governance performance could be improved if these issues were resolved and if the local people were involved in the governance of the Lake Basin. The study concluded with recommendations to integrate local people's perceptions in governance and management decision-making as well as highlighting some issues that arose from the study like a single formal management and policy harmonization organization for the Basin and livelihood support for the local people to reduce environmental degradation.